Transverse Deformation of Long Bones in Vivo During Lag Screw Application - Hutzschenreuter, P.; Bubeck, J. O.; Bruemmer, H. (Veterinary and Comparative Orthopaedics and Traumatology, 1988)
Under in vivo conditions, the transverse deformation of 11 sheep metacarpi was measured, with a special measuring device after insertion of a cortical screw as a lag screw. The outer diameter of a metacarpus in caudocranial direction in the area of the diaphysis is normally 12.98 ±0.44 mm. With a torque moment of 2 Nm, the outer diameter changed by minus 50.53 ± 14.58 (imwhen the cortex screw was inserted. Ten minutes later, the value had become minus 42.43 ± 13.3 nm. These and previous experiments have shown that a lag screw should not be tightened fully upon insertion, but retightened 2-3 times to obtain maximum stabilization of the fracture surfaces.
Keywords: Cortical screw; Lag screw principle; Transverse deformation; Sheep metacarpus